Rmr6 Maintains Meiotic Inheritance of Paramutant States in Zea mays - Hollick, Jay B. (Copyright © 2005 by the Genetics Society of America, 2005)
Paramutation generates heritable changes affecting regulation of specific alleles found at several Zea mays (maize) loci that encode transcriptional regulators of anthocyanin biosynthetic genes. Although the direction and extent of paramutation is influenced by poorly understood allelic interactions occurring in diploid sporophytes, two required to maintain repression loci (rmr1 and rmr2), as well as mediator of paramutation1 (mop1), affect this process at the purple plant1 (pl1) locus. Here we show that the rmr6 locus is required for faithful transmission of weakly expressed paramutant states previously established at both pl1 and red1 (r1) loci. Transcriptional repression occurring at both pl1 and booster1 (b1) loci as a result of paramutation also requires Rmr6 action. Reversions to highly expressed, nonparamutant states at both r1 and pl1 occur in plants homozygous for rmr6 mutations. Pedigree analysis of reverted pl1 alleles reveals variable latent susceptibilities to spontaneous paramutation in future generations, suggesting a quantitative nature of Rmr6-based alterations. Genetic tests demonstrate that Rmr6 encodes a common component required for establishing paramutations at diverse maize loci. Our analyses at pl1 and r1 suggest that this establishment requires Rmr6-dependent somatic maintenance of meiotically heritable epigenetic marks.